If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(1 + -2y) + 5y = 3 (1 * 2 + -2y * 2) + 5y = 3 (2 + -4y) + 5y = 3 Combine like terms: -4y + 5y = 1y 2 + 1y = 3 Solving 2 + 1y = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 1y = 3 + -2 Combine like terms: 2 + -2 = 0 0 + 1y = 3 + -2 1y = 3 + -2 Combine like terms: 3 + -2 = 1 1y = 1 Divide each side by '1'. y = 1 Simplifying y = 1
| 9y-2y+8=4y+38 | | 200-7x=95 | | 3025=x^2+.5625x^2 | | 5k-8=13-2k | | 2?5=-z?45 | | 10w-4w-w+2+w+9= | | 9x-(7x+6)=6 | | 2(3x-4)-10=5(x+4) | | (17x)^(1/2) | | 3025=x^2+1.7778x^2 | | 6=-1?2n | | f(x)=3sinx+4x-1 | | 6+(-3k)-24+13k-(-1)= | | 18y+1=67 | | 3x+8=2x+4fory | | 4x-15=-75 | | 3-3(7-8x)=0 | | 3-2(x+5)=17 | | (6s-5t)(6s+5t)= | | -9(4a+2)+4= | | y^2+1.7778y^2=3025 | | .5(2p-3)-4p= | | 5.88x= | | -4+11k-10+(-17k)+3= | | 2x=y-6 | | (x+1)(x-1)(-5x-2)= | | 2(5-x)=6-(2x-4) | | 3-9(5x+2)=8 | | -7x=2/3 | | -k-(-5k)+9+2k-14= | | 14xy+7x-2y=0 | | 3(5a+3)-6= |